Diagnostic role of ovarian – adnexal reporting and data system magnetic resonance imaging scoring system for evaluation of indeterminate adnexal lesions - Karki, Prabhat; Sherpa, Ngawang Temba; Gautam, Dipti; Ghimire, Prabeen (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Magnetic resonance imaging (MRI) plays an important role in distinguishing malignant from benign adnexal mass which are indistinguishable from ultrasonography. This can help in early diagnosis and treatment of indeterminate adnexal lesions. This study aims to evaluate the features suggestive of malignant features and  accuracy of ovarian adnexal reporting and data system (O-RADS) MRI score in distinguishing benign from malignant lesions when compared with histopathology which is gold standard.Method: This was a retrospective study of MRI pelvis carried out in patients with indeterminate adnexal lesions who had MRI pelvis done from 2018 to 2022 at Patan Hospital, Lalitpur, Nepal.  Ethical approval was obtained from the institutional review committee of Patan Academy of Health Sciences. MRI diagnosis based on O-RADS MRI score was compared with histopathology diagnosis and sensitivity, specificity was calculated. Chi square test was computed and p-value less than 0.05 was considered statistically significant.Result: Among 175 patients, 135 had benign and 40 had malignant lesions. Malignancy was common in middle aged patients (41-60years).MRI features of malignancy were multilocular, solid cystic lesion with contrast enhancement, septations and diffusion restriction. Significant statistical association of O-RADS MRI score was found with histopathology diagnosed malignancy.  92.5% of malignancy had O-RADS MRI score of 4 and 5.The sensitivity and specificity of MRI diagnosing indeterminate lesion was 92.5% and 91.85% respectively.Conclusion: O-RADS MRI scoring is significantly associated with histopathology proven adnexal malignancy hence helps in accurately diagnosing indeterminate adnexal lesions and stratisfying the risk of malignancy.